Identifikasi Natrium Siklamat dan Karakterisasi Bobot Jenis Pada Sampel Minuman Jajanan yang Dijual di Kota Pontianak - Andi Andi; Hadi Kurniawan; Fajar Nugraha (Indonesian Journal of Pharmaceutical Education, 2023)
Food additives are materials that are added in the food and beverages which has function to influence the quality and form of the food. Sodium cyclamate is one of a food additives that commonly used as a sweeteners in beverages, but the excessive and continuous use can cause dangerous effects to the body. The purpose in this study are to identify sodium cyclamate content qualitatively and to determine the density characteristics of the beverages that are sold in the Pontianak city. The method that are used in this reseacrh is descriptive non-experimental using 5 samples of beverages that are sold in the Pontianak City with purposive sampling technique. Identification of sodium cyclamate in beverages samples is carried out qualitatively using HCl, BaCl2, and NaNO2. Samples which positively contain sodium cyclamate will make white precipitate after the reaction. Characterization of the density of beverages samples is carried out using a pycnometer. The qualitative test result in this research indicate that there are 3 out of 5 samples positive containing sodium cyclamate which is samples of beverages C, D, and E. Density result in sample of beverages C, D, and E respectively are 1,0073 g/mL, 1,0075 g/mL dan 1,0086 g/mL.